Overexpression of AtSHN1/WIN1 provokes unique defense responses. - Dikla Sela (PLoS ONE, 2013)
The plant cell cuticle serves as the first barrier protecting plants from mechanical injury and invading pathogens. The cuticle can be breached by cutinase-producing pathogens and the degradation products may activate pathogenesis signals in the invading pathogens. Cuticle degradation products may also trigger the plant's defense responses. Botrytis cinerea is an important plant pathogen, capable of attacking and causing disease in a wide range of plant species. Arabidopsis thaliana shn1-1D is a gain-of-function mutant, which has a modified cuticular lipid composition. We used this mutant to examine the effect of altering the whole-cuticle metabolic pathway on plant responses to B. cinerea attack. Following infection with B. cinerea, the shn1-1D mutant discolored more quickly, accumulated more H2O2, and showed accelerated cell death relative to wild-type (WT) plants. Whole transcriptome analysis of B. cinerea-inoculated shn1-1D vs. WT plants revealed marked upregulation of genes associated with senescence, oxidative stress and defense responses on the one hand, and genes involved in the magnitude of defense-response control on the other. We propose that altered cutin monomer content and composition of shn1-1D plants triggers excessive reactive oxygen species accumulation and release which leads to a strong, unique and uncontrollable defense response, resulting in plant sensitivity and death.